FORMULASI EKSTRAK ETANOL BUAH PARE DAN DAUN PEPAYA SEBAGAI LOSION REPELAN Aedes aegypti - Gratia Apulina Cindylawsa Purba; Delisma Marsauli Simorangkir; Tio Ranti Sari Br Sembiring; Putri Anggita (Jurnal Penelitian Farmasi & Herbal, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus from the genus Flavivirus and the family Flaviviridae, transmitted through the bites of Aedes aegypti and Aedes albopictus. One preventive measure can be achieved by using mosquito repellent lotion as a protective topical preparation. Bitter melon and papaya leaves contain flavonoids and antioxidants that have potential as natural repellent agents. This study aimed to evaluate the effectiveness of lotion formulations containing bitter melon and papaya leaf extracts at concentrations of 0%, 2%, 4%, and 6%. The research method included preparing lotion formulations based on an oil-in-water emulsion, followed by physical quality testing according to SNI 16-4399-1996, including assessments of homogeneity, emulsion type, two-week stability, and skin irritation. Repellent effectiveness was tested by observing the number of mosquitoes that died after contacting skin treated with the lotion. The results show that all formulations meet the physical quality requirements, are homogeneous, stable, possess an oil-in-water emulsion type, and do not cause skin irritation. The extracts increase mosquito repellency, as indicated by the greater number of dead mosquitoes with higher extract concentrations. The 6% formulation is the most effective concentration as a repellent or insecticidal agent against Aedes aegypti.